Evaluating the impact of ecological factors on the quality and habitat distribution of Lonicera japonica Flos using HPLC and the MaxEnt model - Cheng, Jiali; Guo, Fengxia; Wang, Liyang; Li, Zhigang; Zhou, Chunyan; Wang, Hongyan; Liang, Wei; Jiang, Xiaofeng; Chen, Yuan; Dong, Pengbin (Frontiers in Plant Science, 2024)
The quality of Traditional Chinese Medicine by the content of their secondary metabolites, which varies with habitat adaptation and ecological factors. In this study, we established a new method to evaluate the effects of ecological factors on Lonicera japonica Flos quality based on High performance liquid chromatography fingerprinting technology and MaxEnt models. The MaxEnt model was employed to scrutinize the suitable habitat areas for current and future L.onicera japonica Flos. High performance liquid chromatography coupled with the software for similarity evaluation of chromatographic fingerprints of Traditional Chinese Medicine was used to obtain standard High performance liquid chromatography fingerprinting. 21 common peaks were identified, and the contents of five compounds Hyperoside, Rutin, Chlorogenic acid, Cynaroside, Isochlorogenic acid A in these common peaks were determined using the standard samples. Based on High performance liquid chromatography fingerprint and MaxEnt model, a correlation model between ecological factors and chemical composition was established to obtain the potential distribution of high-quality Lonicera L. japonica Flos Through the spatial analysis function of ArcGIS, the Lonicera L. japonica Flos quality zoning map was refined by amalgamating the potential habitat suitability distribution map and the correlation model. The outcomes of this study, which utilized a multivariate information combining approach, offer insights for the examination of other Chinese herbal medicines and the selection of Lonicera L. japonica Flos planting and production areas.